Galectin-3 deficiency drives lupus-like disease by promoting spontaneous germinal centers formation via IFN-γ - Beccaria, Cristian Gabriel (2018)
Germinal centers (GC) are important sites for high-affinity and long-lived antibody induction. Tight regulation of GC responses is critical for maintaining self-tolerance. Here, we show that Galectin-3 (Gal-3) is involved in GC development. Compared with WT mice, Gal-3 KO mice have more GC B cells and T follicular helper cells, increased percentages of antibody-secreting cells and higher concentrations of immunoglobulins and IFN-γ in serum, and develop a lupus-like disease. IFN-γ blockade in Gal-3 KO mice reduces spontaneous GC formation, class-switch recombination, autoantibody production and renal pathology, demonstrating that IFN-γ overproduction sustains autoimmunity. The results from chimeric mice show that intrinsic Gal-3 signaling in B cells controls spontaneous GC formation. Taken together, our data provide evidence that Gal-3 acts directly on B cells to regulate GC responses via IFN-γ and implicate the potential of Gal-3 as a therapeutic target in autoimmunity.